1993
DOI: 10.1515/dma.1993.3.2.191
|View full text |Cite
|
Sign up to set email alerts
|

On the entropy values of hereditary classes of graphs

Abstract: The entropy of a class of graphs is defined as lim n^o o(log x n )/(log y n ), where x n is the number of graphs with n vertices from this class and y" is the number of all graphs with n vertices. In this paper the exhaustive description of the range of values of entropy for hereditary classes of simple graphs is given and a method of evaluation of the entropy for such classes is derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
205
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(206 citation statements)
references
References 1 publication
1
205
0
Order By: Relevance
“…(An extension of this result to all hereditary graph classes was obtained independently by Alexeev [1] and by Bollobás and Thomason [7]. For recent work in this area see [4,2,5].)…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…(An extension of this result to all hereditary graph classes was obtained independently by Alexeev [1] and by Bollobás and Thomason [7]. For recent work in this area see [4,2,5].)…”
Section: Introductionmentioning
confidence: 73%
“…For recent work in this area see [4,2,5].) Recently, an asymptotic version of Conjecture 1.1 was established by Loebl, Reed, Scott, Thomason and Thomassé [22], involving the quantity | Forb(H) n | estimated in (1). We say that a graph H has the asymptotic Erdős-Hajnal property if there exists a constant ε = ε(H) > 0 such that…”
Section: Introductionmentioning
confidence: 99%
“…Scheinerman and Zito ( [23]) showed that |P n | belongs to one of few possible classes of functions. Several other papers sharpen these results, concentrating on, e.g., sparse hereditary properties (Balogh, Bollobás and Weinreich [8], [9]), dense hereditary properties (Bollobás and Thomason [10], [11] and Alekseev [1]) and properties of the type P * H (Prömel and Steger [20] , [21], [22]). …”
Section: Related Workmentioning
confidence: 99%
“…by the colouring number theorem [2,9,6,4]. Similar argument holds for graphs G with α-tw(G) ≤ k. Lemma 2.6.…”
Section: 6mentioning
confidence: 72%